Analisis Massa Penyimpanan Biogas Dengan Variasi Diameter Karbon Aktif Hasil Dari Proses Steam Activation - Wibawa, I Made Satria; Wijaksana, Hendra; Sucipta, Made (Teknik Desain Mekanika, 2022)
Abstract Simantri is an innovation that develops technology that innovates the community for village progress. Simantri activities include increasing the number of livestock populations, planting area, and the quality of the products produced. Cow dung waste from Simantri can be used as biogas as fuel to turn on the stove. The use of biogas for the wider community has not been optimal due to the limited distribution of biogas. This research is expected to find out the potential of using bamboo waste to become an adsorbent as a medium for storing biogas with the ANG (Adsorption Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 Psi with 70 grams of bamboo activated carbon as the adsorbent, the activated carbon was varied with mesh sizes of 35-45, 45-70, and 70-230 at an carbonization and activation temperature of 625oC. The results of the study in biogas storage showed that the highest mass absorption occurred in the 70-230 mesh variation which was able to store 36.6 grams of biogas. Keywords: bamboo, biogas, ANG, activated carbon, mesh sizes activated carbon